The Impact of Collaborative Learning and Personality on Satisfaction in Innovative Teaching Context - Cheng, Fei-Fei; Wu, Chin-Shan; Su, Po-Cheng (Frontiers in Psychology, 2021)
Flipped teaching is one of the most popular innovative teaching methods which has attracted a lot of attention and lead to amount of discussion in recent years. Many educators have generally encountered same doubt when implementing flipped education: Is this kind of teaching mode only applicable to students with high learning achievements? In addition, collaborative learning is often applied in flip teaching and it is also an issue worth to explore. In this study, both quantitative and qualitative studies were conducted to examine the potential factors in affecting the learners’ satisfaction in flipped education. The survey results from 171 participants showed that collaborative learning and need for cognition are significant predictors of learning satisfaction. In addition, a deeper look at the collaborative learning process was further examined by conducting deep interview. A total of 12 students from 6 different flipped-teaching courses participated the interview. The findings suggested that arranging some activities to encourage students to know each other before class that helps students find corresponding group and facilitates their expertise for collaborative learning. The mechanism significantly influenced team members’ engagement, discussion atmosphere, and efficiency. In addition, when learning tasks diversity, it will also enhance students’ innovative ability, empathy, and even promote mutual learning.